A standardised static in vitro digestion method suitable for food - an international consensus - Minekus M; Alminger M; Alvito P; Ballance S; Bohn T; Bourlieu C; Carriere F; Boutrou R; Corredig M; Dupont D; Dufour C; Egger L; et al. (Royal Society of Chemistry)
Simulated gastro-intestinal digestion is widely employed in many fields of food and nutritional sciences, as conducting human trials are often costly, resource intensive, and ethically disputable. As a consequence, in vitro alternatives that determine endpoints such as the bioaccessibility of nutrients and non-nutrients or the digestibility of macronutrients (e.g. lipids, proteins and carbohydrates) are used for screening and building new hypotheses. Various digestion models have been proposed, often impeding the possibility to compare results across research teams. For example, a large variety of enzymes from different sources such as of porcine, rabbit or human origin have been used, differing in their activity and characterization. Differences in pH, mineral type, ionic strength and digestion time, which alter enzyme activity and other phenomena, may also considerably alter results. Other parameters such as the presence of phospholipids, individual enzymes such as gastric lipase and digestive emulsifiers vs. their mixtures (e.g. pancreatin and bile salts), and the ratio of food bolus to digestive fluids, have also been discussed at length. In the present consensus paper, within the COST Infogest network, we propose a general standardised and practical static digestion method based on physiologically relevant conditions that can be applied for various endpoints, which may be amended to accommodate further specific requirements. A frameset of parameters including the oral, gastric and small intestinal digestion are outlined and their relevance discussed in relation to available in vivo data and enzymes. This consensus paper will give a detailed protocol and a line-by-line, guidance, recommendations and justifications but also limitation of the proposed model. This harmonised static, in vitro digestion method for food should aid the production of more comparable data in the future.
Keywords: Science & Technology; Life Sciences & Biomedicine; Biochemistry & Molecular Biology; Food Science & Technology; BIOCHEMISTRY & MOLECULAR BIOLOGY; FOOD SCIENCE & TECHNOLOGY; SIMULATED GASTROINTESTINAL PROTEOLYSIS; PARTICLE-SIZE DISTRIBUTION; GASTRIC LIPASE; BETA-LACTOGLOBULIN; NATURAL FOODS; TEST MEAL; LIPOLYSIS; HUMANS; SECRETION; BEHAVIOR; 0908 Food Sciences